Using Gamification in Teaching Mathematics - Arandoga, Lourey Jhon (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effectiveness of Gamified Physical Games (GPGs) as an intervention tool in teaching Mathematics among Grade 6 students of Sapang Ama Integrated School during the Academic Year 2024–2025. Guided by the gamification framework of Landers and Landers (2014), the study utilized a one-group quasi-experimental pretest-posttest research design to determine the impact of GPGs on students’ mathematical achievement and attitudes toward Mathematics. The respondents consisted of 31 Grade 6 students who participated in a five-week intervention integrating 25 gamified physical games into Mathematics instruction. The study employed a validated 50-item Mathematics achievement test and the TIMSS 2019 Mathematics Attitude Questionnaire (Martin et al., 2020) as research instruments. Data were analyzed using arithmetic mean, weighted mean, paired-samples t-test, and Pearson Product-Moment Correlation. Findings revealed that students’ Mathematics performance significantly improved after the intervention, with mean scores increasing from Low Mastery during the pre-test to Near Mastery during the post-test. Results further indicated a significant difference between pre-test and post-test scores, demonstrating the effectiveness of GPGs in enhancing mathematical achievement. Students maintained a positive attitude toward Mathematics before and after the intervention; however, no significant change in attitude was observed. Moreover, the relationship between students’ attitudes and Mathematics achievement showed a weak positive but non-significant correlation. The study concluded that Gamified Physical Games are effective instructional tools that make Mathematics learning more engaging, interactive, and meaningful for learners. The study recommended integrating GPGs into Mathematics instruction and providing teachers with professional development opportunities related to gamified learning strategies. The study supports Sustainable Development Goal 4 (Quality Education) by promoting inclusive, engaging, and effective learning strategies that improve students’ mathematical achievement and classroom participation. It also contributes to sustainable educational practices by encouraging innovative and learner-centered instructional approaches that can strengthen long-term academic engagement and teaching effectiveness in basic education.
Keywords: Attitude Towards Mathematics; Gamified Physical Games; Grade 6 Students; Mathematics Achievement; Mathematics Instruction; One-Group Pretest-Posttest Design; Quasi-Experimental Design; Student Engagement; Teaching Mathematics